Genetic variation on internal protein matric (M1) and non structural protein (NS1) of Indonesian avian influenza virus H5N1 subtype - N.L.P. Indi Dharmayanti (Jurnal Ilmu Ternak dan Veteriner, 2011)
The mutation and genetic variation of avian influenza virus ussually associated with Hemmaglutinin (HA) and Neuraminidase (NA). The HA and NA protein are surface glycoproteins which have role for receptor binding site of the virus, determine virus subtype and genetic variation occured in those proteins. On the other site, the virus have the internal protein that posses  function for virus replication. This study analyzed the mutation on the the internal protein virus especially the Matrix (M1) and non structural (NS1) protein and its three dimensioanal structure of proteins. The methods used in this study were virus propagation, (Reverse Transcriptase Polymerase Chain Reaction) RT-PCR sequencing of M1 and NS1 and using DS Modeller dan  DS Standalone from Discovery Studio for Modeling and Simulation to predict the three dimentional structure of the proteins. The result of this study showed that Indonesian AI H5N1 subtype had genetic variation internal protein and have no change on conserved of condition such as putative zinc finger and nuclear localization signal (NLS). Genetic variation that occured on PDZ motif of NS1 especially have human origin motif that might be correlated with virus adaptation on human. Key Words: Avian Influenza, Matrix (M1), Non Structural (NS1), Genetic Variation